Acute cholecystitis secondary to Haemophilus parainfluenza: a rare occurrence - Bodden, Chloe; Cristell, Nicole; Alla, Mrinalini; Quang, Camille Mai-Phuong Tran; Louis, Martine A.; Shakil, Javeria (International Surgery Journal, 2026)
This case report is intended to contribute to the medical community’s knowledge of the rare occurrence of Haemophilus parainfluenzae (HPI) isolated from bile fluid in a 66-year-old male with acute cholecystitis complicated by septic shock. HPI, has predominantly been known as an oropharyngeal commensal bacterium, but it’s emergence to be recognized as an opportunistic pathogen may have been under exaggerated. The patient’s clinical course included an initial expected presentation of abdominal pain, sudden deteriorating condition complicated by septic shock and complications demanded for flexible yet meticulous clinical management. Clinical course continues with successful percutaneous cholecystostomy tube placement, and close multidisciplinary management involving surgery, infectious disease and cardiology. This case report serves as an opportunity to consider unexpected infectious organisms in biliary infections, a documentation of clinical resilience, and especially in patients with significant interplaying comorbidities. Additionally, the discussion elaborates on the growth requirements of HPI in bile fluid, emphasizing the significance of factor V for its proliferation.